2009
DOI: 10.1016/j.cam.2008.10.055
|View full text |Cite
|
Sign up to set email alerts
|

A capacity scaling heuristic for the multicommodity capacitated network design problem

Abstract: a b s t r a c tIn this paper, we propose a capacity scaling heuristic using a column generation and row generation technique to address the multicommodity capacitated network design problem. The capacity scaling heuristic is an approximate iterative solution method for capacitated network problems based on changing arc capacities, which depend on flow volumes on the arcs. By combining a column and row generation technique and a strong formulation including forcing constraints, this heuristic derives high quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Similarly, SACG2 produces results that are better by 0.04%. We also note that we are unable to consider the result of SACG2 for instance 30,520,400FT as this value is lower than the lower bound 150009 reported by Katayama et al (2009), and any comparison for this instance would therefore be misleading.…”
Section: Comparative Analysismentioning
confidence: 54%
See 2 more Smart Citations
“…Similarly, SACG2 produces results that are better by 0.04%. We also note that we are unable to consider the result of SACG2 for instance 30,520,400FT as this value is lower than the lower bound 150009 reported by Katayama et al (2009), and any comparison for this instance would therefore be misleading.…”
Section: Comparative Analysismentioning
confidence: 54%
“…In this section, we report comparative computational results of the proposed algorithm with the Cycle-based Tabu Search (CTS) of Ghamlouche et al (2003), Path Relinking (PR) by Ghamlouche et al (2004), Multilevel Cooperative Algorithm (MCA) by Crainic et al (2006), Capacity Scaling Heuristic (CSH) by Katayama et al (2009), IP Search (IPS) by Hewitt et al (2010), the two algorithms based on Simulated Annealing and Column Generation (SACG1 and SACG2) described by Yaghini et al (2013) the results for which are reported with time limits 600 and a 18000 seconds, respectively, and Local Branching (LocalB) by Rodríguez-Martín and Salazar-González (2010). The algorithm described by Alvarez et al (2005) could not be included in the comparisons as the authors do not report any results with the instances tested here; instead they use their own benchmark instances.…”
Section: Comparative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We derive the instances used in our computational study from the C and C+ instances described in detail in Crainic et al (2001). These instances have been used to benchmark the performance of many algorithms for the capacitated fixed charge network design problem (Ghamlouch et al 2003, Ghamlouch et al 2004, Katayama et al 2009, Hewitt et al 2010, Yaghini et al 2012. The instances vary with respect to the number of nodes (20, 30), arcs (230,300,520,700), commodities (40,100,200, and 400), whether the variable costs, c ij , outweigh the fixed costs, f ij , and whether the arcs are loosely or tightly capacitated.…”
Section: Instancesmentioning
confidence: 99%
“…Construction cost of the network is traded-off against delay, or against the total sum of travel distances of the commodities. Frequently, there are additional requirements or constraints; for example, the problem may include limited capacity arcs, stochastic demand, survivability requirements, and so on [18][19][20][21]. The NDP has also been proven to be NP-complete even for simple cases [22].…”
Section: Introductionmentioning
confidence: 97%